Noncognitive skills in economics: Models, measurement, and empirical evidence - Hendrik Thiel; Stephan L. Thomsen (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2009)
There is an increasing economic literature considering personality. This paper provides an overview on the role of these skills regarding three main aspects of economic analysis: measurement, theoretical modeling, and empirical estimates. Based on the relevant literature from different disciplines, the common psychometric measures used to assess personality are discussed. A recently proposed theoretical framework of human capital production takes personality explicitly into account. It is reviewed to clarify the understanding of crucial features of skill development. Based on these foundations, the main results of the empirical literature regarding noncognitive skills are classified along the research questions and summarized.
More recent version: http://hdl.handle.net/10419/54966
Keywords: I20; I28; J12; J24; J31; 330; noncognitive skills; personality; human capital formation; psychometric measures; Persönlichkeitspsychologie; Kognition; Qualifikation; Bildungsinvestition; Theorie; Welt